(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
200 samples of barley varieties were studied in the irrigated lands of the Samarkand region, and they were complexly evaluated. From them, productive, productive, resistant to lodging, resistant to unfavorable environmental factors, early ripening varieties with high productivity, resistant to diseases were selected.